The functions f (x), g(x), and h(x) are defined below.

F(x)=3x
G(x)=10x+4
H(x)=x^2-x
Which expression is equivalent to (h-f)(-3)

1 answer

(h-f)(x) = h(x) - f(x) = (x^2-x)-(3x) = x^2 - 4x

Now plug in x = -3 and maybe one of your choices will match.
Similar Questions
  1. Unicellular cells must carry out ___ of life.(1 point)Responses specific functions specific functions a few functions a few
    1. answers icon 7 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. goo.gl/photos/2RPU1dAWoKzUn4Pf81. Which of the above functions are not continuous where they are defined? Why? 2. Which of the
    1. answers icon 1 answer
more similar questions